Digitalization beyond technology: Proposing an explanatory and predictive model for digital culture in organizations - Antonio L. Leal-Rodríguez; Carlos Sanchís-Pedregosa; Antonio M. Moreno-Moreno; Antonio Leal-Millan (Journal of Innovation & Knowledge (JIK), 2023)
Continuous technological advancements and digitalization are transforming organizations' resources and capabilities, yet many have not adapted their corporate culture accordingly. Aligning with a digital-oriented culture archetype is crucial for successful digital transformation. This paper presents a research model that predicts digital culture in organizations based on traditional culture archetypes. Using cutting-edge multivariate analysis techniques, such as PLS-SEM, IPMA, or PLS-Predict, on a sample of 285 managers from Spanish companies, the results indicate that a People-oriented culture archetype is the most important for digital culture, while values inherent to Norms or Goals culture archetypes hinder it. The paper contributes to the development of Functionalist and Structuralist Theories of culture, demonstrating the interplay of micro-cultures and cultural archetypes within an organization.
Keywords: 650; Digital culture; Digitalization; Organizational culture